If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 + -10c = 100 Add '-100' to each side of the equation. 100 + -100 + -10c = 100 + -100 Combine like terms: 100 + -100 = 0 0 + -10c = 100 + -100 -10c = 100 + -100 Combine like terms: 100 + -100 = 0 -10c = 0 Solving -10c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-10'. c = 0 Simplifying c = 0
| 10+x=32-4 | | 3a+8b+7a-b= | | 15x-8-10x+6=53 | | 6g=17 | | 7x+4(3-5x)=0 | | 4m+7=51 | | 18y*18y-18y-16y*16y+12y-15= | | Y=2x128/52 | | 2(3x-4)=3x+25 | | 5x+13=-5(2+2x)-8x | | -50.5+-96.8-1.6y+24.2+y=190 | | eln(2x-3)=1 | | 5+x-3=3x | | Y=2x4-128/152 | | 12c-7-3c+9= | | 6x^2-36x-96=0 | | 8z+6z= | | 2ln(2x-3)=2 | | 32=-16t+56t | | x^2+y^2+12x+4y+36=0 | | 2s+7s= | | 21y+7y= | | 2x+x+10=55 | | 86x+5x-8y-800=500 | | 5p+5p= | | 3x(x-2)=-1.5 | | 13b+7b= | | 4w+2=4w+7 | | 2x+8-3=11+11+11 | | w*3=7 | | 29r+4=28+1r | | (w/(2w-3))=4/w |